ADENOVIRUS VECTOR SYSTEM: A POTENTIAL TOOL FOR INTRODUCING ANTIGENIC GENE IN PRODUCTION OF NEW GENERATION VACCINES - Hoà, Lê Thanh (Vietnam Journal of Biotechnology, 2011)
Viral vector based vaccines generated by genetic engineering are able to produce three kinds of immune responses: humoral immune response, cell-mediated immune response and mucosal immune response. Administrative routes for viral vector based vaccines are feasible over other ones, of which the biggest advantage for these kinds of vaccines is easily to introduce antigen to animal population in the simplest way without needle; and is cost-effective by the alimentary (by feeding/drinking) and respiratory (by aerosol) application. The adenoviral vector systems are potential sources to provide common vectors for biomedical usage as gene-transferring vehicles: for new generation vaccines to induce immunity; for expression of cytokines in enhancing immunity; for RNAi (RNA interference) to silence the target genes; and particularty, for genetic therapy as targeting vectors widely used against cancerous and contagious diseases. There are a number of adenovims based vectors to be constracted as antigenic transferring tools. In terms of materials, three initiative kinds required include source of plasmid DNA originated from genome of a donor adenoviras; source of plasmid DNA vector used as a vehicle to shuttle the target gene(s); and accessory components including bacterial and mammalian cell systems for assemblying vaccine-candidate recombinant adenovirases. In terms of principle, a vaccine-candidate recombinant adenoviras must meet the requirements that they well replicate in permissive cells for provision of high quantity/quality for vaccine production; and is able to induce immunity (immunogenicity) in immunization of the particular vaccines. In this paper, we introduce the most characteristic features of adenovirases in the family Adenoviridae; the most basic principles and methodologies for generation of a vaccine-candidate recombinant adenovirus habouring an antigenic gene; and the successfiilly constracted adenoviras-based vectors for a number of recombinant vaccines for human and animals.